AN ANALYSIS OF CHARACTER NEEDS IN NAGUIB AL-KILANI'S NOVEL “AR-RAJUL ALLADZI AMANA” BASED ON ABRAHAM MASLOW'S MODEL - Rabbani, Muhammad Yasyfa; Fransisca, Malia (Journal of Arabic Language and Literature (ALLAIS), 2024)
Abstract This study analyzes the character needs in the novel Ar-Rajul Alladzi Amana by Naguib Al-Kilani using Abraham Maslow's humanistic psychology theory. The study aims to identify the types of character needs and explain how these needs influence character development within the narrative. The research employs a descriptive qualitative method, using primary data in the form of selected excerpts from the novel. Data collection is conducted through library research techniques, analyzed based on Maslow's five levels of needs: physiological needs, safety needs, love and belonging needs, esteem needs, and self-actualization needs. The results reveal that the characters in the novel reflect physiological needs for survival, safety needs for protection, love needs for acceptance, esteem needs for self-worth, and self-actualization needs as the pinnacle of character aspirations. The novel highlights the complexity of these needs and their impact on character interactions within their environment.